Clean energy from salinity gradients using pressure retarded osmosis and reverse electrodialysis: A review. (February 2022) - Sharma, Mukesh; Das, Pranjal P.; Chakraborty, Arun; Purkait, Mihir K.
Graphical abstract: Highlights: Comparative analysis of the PRO and RED processes for energy extraction using salinity gradients. Advantages of PRO process over RED methodology. Various involved essential parameters have been discussed. Future scope and development of the PRO and RED processes for implementation of the available prototype at field scale. Abstract: Global energy consumption is increasing, highlighting the need for renewable energy sources for power generation. Nonrenewable energy sources, as they are currently employed, are quite likely to go extinct very soon. Pressure retarded osmosis (PRO) and reverse electrodialysis (RED) are two methods of harvesting renewable energy using salinity gradients. These are non-polluting energy sources that can be found at the interface of two solutions with varying salinity gradients. For PRO, salt rejecting membranes are utilized whereas for RED ion-selective membranes are used. PRO membranes involve controlled mixing, whereas ion exchange membranes (IEMs) used in RED utilize the ion flux for tapping energy. This review explains that PRO has an upper hand over RED, as it demonstrated higher power densities (22–32 times) than RED for engineered salinity gradients, and performs a comparative analysis taking into account critical parameters such as membrane materials used, modifiers involved, different essential parameters, and power density, all of which are thought to have a significant impact on performance. A researcher would easily grasp why PRO is thought to offer an added benefit over the RED procedure for harnessing salinity gradient energy after reading this review.